An analysis of economic incentives to encourage organ donation: Evidence from Chile - Marcela Parada-Contzen; Felipe Vásquez (Latin American Economic Review, 2019)
We perform a cost-benefit analysis on the introduction of monetary incentives for living kidney donations by estimating the compensation that would make an individual indifferent between donating and not donating a kidney while alive using Chilean data. We find that monetary incentives of US12,000 save US38,000 to health care system per donor and up to US169,871 when we consider the gains in quality of life of receiving an organ. As one allows the incentives to vary depending on the individual position on the wage distribution, the compensation ranges from US4214 to US83,953. Importantly, introducing payments to living donors payable by a third party helps patients who currently may not have access to necessary medical treatment. Therefore, exclusions in access for organs due to the monetary constraints can be prevented.
Keywords: I18; K32; D61; 330; Organ donation; Compensations to living donors; Cost– benefit analysis